UkrVO Astronomical WEB Services - Mazhaev, O.E. (Science and Innovation, 2024)
Ukraine Virtual Observatory (UkrVO) has been a member of the International Virtual Observatory Alliance (IVOA) since 2011. The virtual observatory (VO) is not a magic solution to all problems of data storing and processing, but it provides certain standards for building infrastructure of astronomical data center. The astronomical databases help data mining and offer to users an easy access to observation metadata, images within celestial sphere and results of image processing. The astronomical web services (AWS) of UkrVO give to users handy tools for data selection from large astronomical catalogues for a relatively small region of interest in the sky. Examples of the AWS usage are showed.